OPTIMAL ENERGY CAPACITIES AND TECHNOLOGIES FOR PERMANENT AND RELIABLE ELECTRICITY SUPPLY, CONSIDERING RISK CONTROL - FABIJAN, Drago; Predin, Andrej (Journal of Energy Technology, 2024)
Inthispaperoptimalenergysourcestructuresforelectricityproduction,throughtheneedsof the system transmission operator (TSO) who is responsibleforsecureandreliablesupply within its own regulating area, as well as over disposable energy fuels, are discussed. Long term reliable electricity energy supplies, system suitability, suitability of production capability, suitability of electricity grid, market suitability and short term secure and reliable supply are considered. Cost risks calculations are given, considering different technologies and sources, using a model of reference price of electric energy. The optimal structure of energy producing resource sistre ate dfromthe pointof view of thetransmission system operator (TSO), primary frequencycontrol,secondaryfrequencycontrolandtertiaryminutecontrol.